An analysis of CAPM efficiency: the case of the DFM market in Dubai. (22nd December 2021) - Corelli, Angelo; Achcar, Siham; Chekanova, Anna; Ghalayini, Rim; Orazalyyeva, Nazli
The project analyses the DFM market in terms of efficiency, by applying portfolio theory to the construction of the efficient frontier and the security market line (SML). Moreover, a SML analysis is performed in order to obtain 'buy' or 'sell' recommendations. The dataset includes 35 companies that are currently listed and showing reliable data evolution over time. The constrained minimisation, not allowing for short selling so to mimic the regulatory environment on DFM, shows that all stocks are below the capital market line. Unconstrained optimisation is not possible due to the variance-covariance matrix not being positive-definite. The SML analysis shows that signals are contradictory and equally split between 'buy' and 'sell', resulting in uncertainty about the future trend of the market.